Pelatihan Troubleshooting Instalasi Linux Debian Dengan Text Mode Dan Graphic Mode Di SMK Negeri 5 Palembang - Al Rivan, M Ezar; Arman, Molavi; Irsyad, Hafiz (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2021)
Community service activities are carried out at SMK N 5Palembang. This training activity aims to improve the competence ofstakeholders in SMK N 5 Palembang, consisting of productive teachers,students and student councils. This activity is carried out by the pratikummethod and question and answer procession about troubleshooting andinstallation both in text mode and graphic mode. The benefits obtained ininstallation training using text mode are very light in operation and quite fastin the installation procession while by using graphic mode is using enoughprocessor and ram resources, thus reducing acceleration and installationspeed.